Heterotrophic consumption may mask increasing primary production fuelled by anthropogenic nutrient loading in the northern Arabian/Persian Gulf. (November 2019) - Al-Said, Turki; Naqvi, S. Wajih A.; Ahmed, Ayaz; Madhusoodhanan, Rakhesh; Fernandes, Loreta; Kedila, Raziya; Almansouri, Hadeel; Al-Rifaie, Kholood; Al-Yamani, Faiza
Abstract: Monthly measurements of nitrate, nitrite, ammonium and phosphate at three stations off Kuwait during 2002–2015 revealed considerable inter-annual variability, broadly corresponding to fluctuations in the Shatt-al-Arab River discharge, but a lack of secular increasing trend. Nutrient enrichment experiments during two seasons revealed nitrate uptake, chlorophyll build-up and growth of micro-phytoplankton, even in the presence of ammonium, provided the availability of phosphate. Primary production was mostly nitrogen limited, but anthropogenic nitrogen supply may eventually make it phosphorus limited, especially in summer and in the open Gulf. Anthropogenic nutrient inputs appear to have enhanced biological productivity of the northern Gulf, but heterotrophic consumption, indicated by high respiration rates, probably prevented accumulation of phytoplankton biomass, accounting for the observed lack of chlorophyll increase over the past three decades. Consequently high total organic carbon and emerging hypoxia in the Gulf may lead to expansion/intensification of the oxygen minimum zone of the Arabian Sea. Highlights: Large interannual changes in nutrients off Kuwait from 2002 to 15, no secular increase Productivity N-limited with potential for P-limitation in summer and in open Gulf High respiration rates imply rapid consumption of photosynthesized organic matter. Nutrient loading enhancing productivity but grazing may control autotrophic biomass. Increased productivity likely to promote deoxygenation in the Gulf and Arabian Sea